Type and token in the prehistoric origins of numbers - Schlaudt, Oliver (Cambridge archaeological journal, 2020)
The type-token distinction and the notion of ‘tokenization’ are proposed as analytical tools that may help us understand better the emergence of numbers and mathematical thinking from the non-mathematical cultural practices of the Upper Palaeolithic such as painting, decorating portable objects, or making ornaments from beads, as described in recent studies in cognitive archaeology. While the type-token distinction has been a salient element in recent debates in the philosophy of mathematics, it seems not yet to have been registered in those areas of cognitive archaeology concerned with numbers—and yet it may help to identify the circumstances under which the conceptual potential of cultural artefacts develops. The concept of tokenization permits us to identify a plausible link between non-numerical cultural resources and the emergence of numerical thought patterns. This approach offers a way of appreciating the role of artefacts without raising the notoriously difficult question of their original ‘meaning’.
Gesehen am 16.10.2020